New evidence guiding extent of lymphadenectomy for esophagogastric junction tumor: Application of Ber-Ep4 Joint with CD44v6 staining on the detection of lower mediastinal lymph node micrometastasis and survival analysis. Issue 14 (April 2017) - Zheng, Bin; Ni, Chen-Hui; Chen, Hao; Wu, Wei-Dong; Guo, Zhao-Hui; Zhu, Yong; Zheng, Wei; Chen, Chun
Abstract : Abstract: For Siewert type II adenocarcinoma of the esophagogastric junction (AEJ), the optimal surgical approach and extent of lymph nodes dissection remain controversial. Immunohistochemistry (IHC) has been reported to be available for identifying lymph node micrometastasis (LNMM) in patients with AEJ. This was a prospective case series of patients who underwent R0 resection and lower mediastinal lymphadenectomy from January 2010 to June 2015 in Fujian Medical University Union Hospital for Siewert type II AEJ. The outcomes were analyzed retrospectively. A total of 1325 lymph nodes were collected from 49 patients, grouped into 3 groups: lower mediastinal, paracardial, and abdominal. The former 2 groups were examined by monoclonal antibodies against Ber-Ep4 and CD44v6. The incidence of LNMM in mediastinal group was 37% (18/49) for Ber-Ep4 and 33% (16/49) for CD44v6. While in routine histological diagnosis, the number of patients with the positive lymph nodes was 7 (14%). When combining IHC with histopathology (HE) staining, the incidence of positive mediastinal lymph nodes was increased to 24%, with a total number of 37 lymph nodes from 28 patients (57%). Micrometastases indicated by Ber-Ep4 and CD44v6 were associated with the depth of tumor invasion ( P = 0.020 and 0.037, respectively), histopathological nodal status ( P = 0.024 and 0.01, respectively), and Lauren classification ( P = 0.038 and, respectively). Expression of CD44v6 and Ber-Ep4 was positively correlated ( r = 0.643, P < 0.001). The 3- and 5-year survival rates for all patients were 66% and 50%, respectively. The patients with LNMM had a lower 3-year survival rate of 51%, compared to 80% from no LNMM group; 5-year survival rate was also lower in LNMM group, which is 29% versus 68% ( P = 0.006) in the no LNMM group. Patients with positive Ber-Ep4 cells had a lower survival, but not statistically significant ( P = 0.058). CD44v6-positive group had a significantly reduced survival ( P < 0.001). In patients group with negative lower mediastinal lymph nodes, patients without LNMM obtained a significant survival benefit ( P = 0.021). Our study demonstrated that routine test for LNMM is necessary for patients with negative lymph nodes. As a positive prognostic factor, thorough lower mediastinal lymphadenectomy in an invasive approach should be considered when necessary. Ber-Ep4 and CD44v6 were shown to be great markers for detecting LNMM.